2016
DOI: 10.1177/0193945916683682
|View full text |Cite
|
Sign up to set email alerts
|

Barriers in Transitioning Patients With Severe Obesity From Hospitals to Nursing Homes

Abstract: This cross-sectional, descriptive study explored perspectives of discharge planners regarding transitions of hospitalized patients who are severely obese seeking discharge to a nursing home. Attention has been focused on care transitions regarding high hospital readmission rates, yet specific needs of patients who are severely obese have been largely overlooked. Ninety-seven (response rate 39.8%) discharge planners returned surveys addressing frequency of, and issues encountered when arranging placements. Comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 28 publications
(41 reference statements)
0
17
0
Order By: Relevance
“…In a recent survey of nursing homes administrators, 31% of respondents reported that staffing was not adequate to care for morbidly obese residents (defined in this study as residents weighing 325 pounds or more), and a survey of hospital discharge planners found that 60% of respondents thought that nursing homes had staffing concerns regarding admission of someone with a BMI of 35 or more. 31,32 While this difference between available workforce and assistance needed may have be compensated for by new methods or technology, it is most likely that staff are using a greater proportion of time and energy caring for the intensive needs of residents with obesity. Resident obesity is leading to a serious workforce issue.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a recent survey of nursing homes administrators, 31% of respondents reported that staffing was not adequate to care for morbidly obese residents (defined in this study as residents weighing 325 pounds or more), and a survey of hospital discharge planners found that 60% of respondents thought that nursing homes had staffing concerns regarding admission of someone with a BMI of 35 or more. 31,32 While this difference between available workforce and assistance needed may have be compensated for by new methods or technology, it is most likely that staff are using a greater proportion of time and energy caring for the intensive needs of residents with obesity. Resident obesity is leading to a serious workforce issue.…”
Section: Discussionmentioning
confidence: 99%
“…31 Among hospital discharge administrators, 72% of respondents reported perceived nursing home concerns regarding equipment necessary for care for residents with a BMI of 35 or more. 32 Such equipment is expensive to purchase or lease, and it may be difficult to justify for nursing homes with lower numbers of residents with obesity, leading nursing homes with less equipment, staffing, or volume to refuse admission to these prospective residents. Indeed, one third of hospital discharge planners reported that nursing homes often or always refuse admission to these residents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In situations where power failures may occur, facilities must consider the needs of people reliant on electric devices and have adequate arrangements for backup power(4042). Additionally, it has been suggested that consideration needs to be given to factoring in the predicted longer evacuation time of larger and older adults(43). Based on our findings, it is imperative that homes develop emergency management plans and procedures that consider the weight and size of residents.…”
Section: Discussionmentioning
confidence: 99%
“…Given that African Americans have the highest prevalence of obesity, it is important to examine what strategies are effective for this group. Transitioning patients with severe obesity from the hospital to a nursing home has its challenges, which is addressed by Bradway, Felix, Whitfield, and Li (2017). Petit Francis, Spaulding, Turkson-Ocran, and Allen (2017) conduct a systematic review to determine whether nurse-delivered weight management interventions improve weight outcomes, which is a unique perspective because weight loss studies are most commonly conducted by behavioral scientists.…”
mentioning
confidence: 99%